Multipolarized Palsar/Alos images to discriminate sugarcane phenological phases - Picoli, Michelle Cristina Araujo (2012)
The objective of this work was to evaluate the potential of multipolarized Palsar/Alos satellite images to discriminate phenological phases of sugarcane. Digital values from four digital images of February, May, August, and October 2008, with HH (sending and receiving wave in horizontal polarization) and HV polarizations (sending wave in horizontal polarization and receiving in vertical polarization), were converted to backscattering coefficients (σ°) for data analysis of sugarcane cultivated in the northeastern of the state of São Paulo, Brazil. Three varieties were selected at different phenological stages: RB85‑5156, six stands; RB86‑7515, ten stands; and RB92‑5345, ten stands. The differences between the phenological phases were analyzed for each variety, and also between varieties. The single or dual‑poralized Palsar/Alos data, obtained in two polarizations, were able of discriminating the different phases of sugarcane growth, except for the grand growth period and maturity phase, in which no significant difference was observed.